Production and quality of Sweet Grape tomato in response to foliar fertilization with boron - Melo,Raphael O (2019)
ABSTRACT Boron (B) fertilizer application for tomato crop can be carried out by applying the nutrient to the soil or by spraying liquid solutions on leaves. The use of different fertilizers containing B can interfere in fertilization efficiency, since the performance of each product can be determined by its physicochemical properties. The aim of this study was to evaluate the application efficiency of two boron-based commercial foliar fertilizers applied at two time intervals and their possible effects on production components of Sweet Grape tomato. An experiment was conducted under commercial hydroponic system in split-split plot scheme that combined two doses of boron in the nutrient solution [sufficient (25 µmol L-1) or insufficient (6.25 µmol L-1)], two intervals between foliar sprays of B (seven or 14-day intervals) and two commercial foliar fertilizers [boric acid (0.34 g L-1) and sodium octaborate (0.36 g L-1)]. A positive effect of boron foliar fertilization was observed on the productivity or on fruit quality when a condition of B deficiency was noticed in plants, without significant difference in effects concerning the two B-source and the frequency of these applications.